2019
DOI: 10.26434/chemrxiv.7962848.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell Adherence and Drug Delivery from Particle Based Mesoporous Silica Films

Abstract: Spatially and temporally controlled drug delivery is important for implant and tissue engineering applications, as the efficacy and bioavailability of the drug can be enhanced, and can also allow for drugging stem cells at different stages of development. Long-term drug delivery over weeks to months is however difficult to achieve, and coating of 3D surfaces or creating patterned surfaces is a challenge using coating techniques like spin- and dip-coating. In this study, mesoporous films consisting of SBA-15 pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The main characteristic of chronic obstructive pulmonary disease (COPD) is an excessively inflammatory response of the lungs to respiratory contaminants, mostly cigarette smoke, which results in restricted airflow. According to WHO's reports, lower respiratory tract infections and COPD are accountable for over 6 million deaths per year [3]. In addition to the pulmonary pathology, COPD is also correlated to multiple extra pulmonary side effects, including systematic inflammation, nutritional abnormalities and muscle dysfunction.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…The main characteristic of chronic obstructive pulmonary disease (COPD) is an excessively inflammatory response of the lungs to respiratory contaminants, mostly cigarette smoke, which results in restricted airflow. According to WHO's reports, lower respiratory tract infections and COPD are accountable for over 6 million deaths per year [3]. In addition to the pulmonary pathology, COPD is also correlated to multiple extra pulmonary side effects, including systematic inflammation, nutritional abnormalities and muscle dysfunction.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Björk and colleagues [ 54 ] produced mesoporous silica thin films from nanoparticles via direct growth method on silicon substrates pre-treated with octa-decyltrichlorosilane [ 94 ]: this approach has the advantage that it allows to grow thin films in 3D directions [ 49 ], without the need of a flat surface to produce the thin films, which is beneficial for surgical implants, e.g., The films were functionalized with –COOH groups soaking them in a 25% water solution of carboxyethylsilanetriol di-sodium salt, in order to increase its hydrophobicity. The COOH-functionalization allowed loading the mesopores with 3,3′-dioctadecyloxacarbocyanine perchlorate (DiO), a small, yellow-fluorescent hydrophobic model drug.…”
Section: Functional Groupsmentioning
confidence: 99%
“…Mesoporous coatings of TiO 2 and SiO 2 have been extensively studied as supports for bone tissue regeneration [ 47 , 52 , 53 ], for controlled in situ drug release, [ 54 , 55 ] or for applications in the field of orthopaedics and dental implants. It was demonstrated that the surface roughness improves eucariotic cell adhesion and growth [ 56 ], while at the same time, bacterial adhesion is reduced on mesoporous surfaces [ 57 , 58 ], making mesoporous coatings useful tools to prevent biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…Functional coatings based on the assembly of submicrometric or nanometric particles (NPs) are found in many applications in biomedical field. For example, it was recently proposed that NPs-based monolayers or multilayers can serve as drug delivery platforms in which physisorbed NPs are loaded with drugs for precise drug delivery and prolonged drug release [ 1 , 2 , 3 , 4 , 5 , 6 ]. NPs-based coatings are particularly fragile and often need to be reinforced before use, for example, by hydrothermal treatments [ 7 , 8 ] or atomic layer deposition [ 9 ].…”
Section: Introductionmentioning
confidence: 99%